Maja Kleczewska’s Hamlet as a Mirror of Contemporary Poznan and Poland - Anna Wołosz-Sosnowska (Polish Journal of English Studies, 2020)
Hamlet is a timeless play, which has been inspiring artists - actors, directors, film makers as well as writers, for over 400 years. The beauty of language, but also the universality of the topics such as revenge, betrayal, struggle for power, love, as well as the role of theatre are the reasons why Hamlet is still so contemporary. Nevertheless, Shakespeare’s plays reveal their full potential when they are staged, but staging Hamlet in the 21st century in Poland, in Poznan is connected with the question ‘why?’. What is the reasoning behind staging this Elizabethan play today? Nowadays the adaptations of Shakespeare’s plays, both on stage and on screen, are not without a reason; the already mentioned universality transforms itself into a comment on socio-political situation. In the play itself, Shakespeare refers to the theatre-mirror metaphor which comments on the reality. By staging Hamlet in Teatr Polski in Poznań (2019) Kleczewska touched upon many contemporary problems of Poznań and Poland. She collected and commented on the anxieties and issues with which we tackle. Multiculturalism, Ukrainian immigration, multiple languages on the streets, feminism, the role of culture are just few topics touched by Kleczewska in the performance, but also topics which make the audience consider their place within the socio-cultural space. The aim of the paper is to indicate and analyse in these elements which occur in the performance.